(untitled) (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-83-95 This article is devoted to the integrative linguistic analysis of the means, expressing motivation in the genre of the university vice-chancellor’s address to the academic community. The study is carried out within the framework of the modern theory of discourse and pragmalinguistics and considers the vice-chancellor’s address as an established, traditional oral speech genre. The article identifies some key approaches to motivation in the professional environment in relation to the academic context, develops an analytical model for employing motivational speech strategies. It also analyzes the dominant motivational strategies at different levels of the language: lexical, morphological-syntactic, textual-compositional, and linguistic-pragmatic. The aim of the study is to identify and systematize the main motivational strategies implemented in the speech practices of the British university vice-chancellors. The results of the study show that the genre of vice-chancellor’s address has specific features due to its status, institutionality publicity, dialogicity, targetting, and genre asymmetry (vice-chancellor → community). The speech producers try to satisfy various motivational needs, such as informing the audience about the university’s mission, prestige, and values; creating a sense of community; demonstrating support and empathy; appealing to challenges as opportunities; giving academic freedom. The strategy of modality plays a special role in expressing motivation as a way of showing the speaker’s attitude towards the content of the utterance, the communicative goals, and the degree of reliability of the information being conveyed. Key words: academic genre, motivational strategies, lexical level, morphological and syntactic level, text-composition level, linguistic pragmatics level, discourse analysis